Analisis Batuan Bawah Permukaan Pantai Kolbano Berdasarkan Data Geolistrik Resistivitas - Yanti Boimau; Angelikus Olla; Hilari F. Lipikuni; Wenti M. Maubana; Hery Leo Sianturi (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2024)
Research has been conducted on mapping subsurface rocks with resistivity geoelectric method at Kolbano Beach. The research aims to map the pattern of rock layers and identify the type of subsurface rock based on the resistivity value and determine the thickness of the rock layers in the study area. Data processing using Res2dinv software. The method used is the schlumberger configuration geoelectric method. The interpretation results show that the rock layer pattern for 4 passes with a track length of 400 meters with variations in resistivity values ranging from 359 Wm -187,433 Wm, 38.5 Wm -8,450 Wm, 133 Wm -17,607 Wm, and 53.7 Wm -63,032 Wm. The identified rocks are aluvium rocks with a resistivity value of 38.5 Wm -800 Wm and limestone rocks with a resistivity value of 801 Wm -187,433 Wm with a thickness of 5.5 m-73.8 m for aluvium rocks and 0 m-73.8 m for gamping rocks, respectively. Based on the rock resistivity value in the research area, the coloured rock which is the mining material in Kolbano Village is classified as an aluvium rock type. Keywords: Schlumberger, Kolbano, Resistivity, color stone